OSTEOPENIA IN MALE AND FEMALE PATIENTS USING CARBAMAZEPIN AND VALPROIC ACID COMBINATION THERAPY: Analysis of Prevalence and Its Relationship with Epilepsy Characteristics - Krisninda Anggonowati; Endang Kustiowati; M.I. Widiastuti; Amin Husni; Aris Catur Bintoro; Rahmi Ardhini (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
ABSTRACT Background : Epilepsy is a chronic condition with unprovoked seizures. One of the changes affected by anti-epileptic drugs is a decrease in bone density. Gender and sex hormones have implications on bone density.Objective : To determine the prevalence difference osteopenia between male and female, and relationship with clinical characteristics epilepsy patients taking a combination of carbamazepine and valproic acid.Methods: A cross-sectional study with 22 epileptic patients with age range of 18-60 years taking combination of carbamazepine and valproic acid at the Neurology Department Dr. Kariadi Semarang during June to October 2021 who met the inclusion and exclusion criteria. Patient data were obtained by filling out a questionnaire. The assessment of osteopenia was carried out by examination of Bone Mineral Densitometry. Data analysis was using Chi Square test and Spearman correlation test. The result was determined to be significant if the p value <0.05.Results : There were 11 male subjects and 11 female subjects. Chi Square resulted in significant difference between male and female (p<0.05). Spearman correlation test showed a relationship between osteopenia and duration before combination therapy, for men rho 0.734 (p<0.05), women rho 0.786 (p<0.001). There was a relationship between osteopenia and the onset of epilepsy, male rho 0.603 (p<0.05), female rho 0.757 (p<0.001). There was a relationship between osteopenia and age, male rho 0.487 (p=0.129), female rho 0.780 (p<0.001). There was also a relationship between osteopenia and seizure frequency, male rho 0.457 (p<0.05), female rho 0.467 (p=0.026).Conclusion: There was a significant osteopenia prevalence difference between male and female epilepsy patients taking combination of carbamazepine and valproic acid. Moderate and strong relationship were found between osteopenia and clinical characteristics epilepsy. Keywords : Epilepsy, osteopenia, carbamazepine, valproic acid